Assessment of the factual supply of athletes` body with micronutrients - Peciukoniene, M.; Stukas, R.; Kemeryte Riaubiene, E.; Baskiene, V. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The aim of the work was to study the factual nutrition of athletes and to assess the supply of micronutrients to their bodies. The study cohort comprised 60 individuals (23 females and 37 males, age range 21-24 years) who combined studies at the Vilnius Pedagogical University with training in sports. Their physical development, daily regime by using a questionnaire were examined.